Isotopic and hydrogeochemical tracking of dissolved nutrient dynamics in the Brahmaputra River System: A source delineation perspective. (November 2022) - Das, Aparna; Kumar, Manish; Jha, Pawan Kumar; Kumari, Rina; Panday, Durga Prasad; Hdeib, Rouya; Mahlknecht, Jürgen; Deshpande, R.D.
Abstract: The Brahmaputra river system (BRS) produces the largest discharge in India, supplying water to more than 62 million inhabitants. The present study aims to quantify the environmental elements that affect the spatio-temporal variation of nutrients in the Brahmaputra river system (BRS). The association of physico-chemical characteristics of floodplain sediments with the distribution pattern of P during wet and dry periods in different depths were also studied. The seasonal variation suggest that the average dissolved inorganic nitrogen and dissolve inorganic phosphorus are found higher in monsoon while the average dissolve silica were higher in post-monsoon. The spatial variation of dissolve inorganic phosphate and nitrate concentration suggests both the nutrient are higher in upstream sites. The DiS concentrations tended to be higher in downstream. In 70% of the sampled tributaries, the average molar ratio for dissolved inorganic nitrogen/dissolved inorganic phosphorous (DIN/DIP) was greater than 16:1, which indicates phosphate limited biological productivity. In contrast, an average molar ratio of dissolved inorganic silica/DIN (DSi/DIN) of 3.8 ± 3.0 favoured diatom growth in those tributaries where DSi/DIN molar ratio was lower than 1, indicating eutrophication. The BRS transported 24.7, 5.93, and 312 × 10 4 tons/year −1 of DIN, PO4 –P and SiO2 –Si, respectively. The depth-wise variation of P -fraction during monsoon suggests that the authigenic phosphorus was most abundant followed by Fe-bound, exchangeable, detrital and organic. In the post-monsoon, Fe-bound P was found at a higher concentration followed by authigenic phosphorus. High nutrient concentrations with more δ 18 O depleted water implied precipitation being the major source of nutrients in the BRS. Graphical abstract: Image 1 Highlights: Characterization of nutrient loads on the Brahmaputra River System (BRS) is carried out. Hydro-geochemistry, P -fractionation, and isotopic ratios are coupled to understand nutrient dynamics. Phosphate limitation and eutrophication, in parts of the BRS were detected. Authigenic phosphorus was most abundant followed by Fe-bound, exchangeable, detrital and organic. High nutrient with depleted δ 18 O water implied precipitation being the major source of nutrients.